EPR and ENDOR detection of compound I from Micrococcus lysodeikticus catalase. - Benecky, M; Frew, J; Scowen, N; Jones, P; Hoffman, B (1993)
We present the first EPR and ENDOR examination of a catalase compound I (Cat I), the one formed by peracetic acid treatment of Micrococcus lysodeikticus catalase. The Cat I rapid-passage EPR signal (g perpendicular eff = 3.32; g parallel eff approximately 2) appears quite different from those reported previously for the compounds I from horseradish peroxidase (HRP I) and chloroperoxidase. Nonetheless, all three signals can be explained by the same model for exchange coupling between an S = 1 oxoferryl [Fe = O]2+ moiety and a porphyrin pi-cation radical (S' = 1/2) (Schulz, C. E., et al. (1979) FEBS Lett. 103, 102-105). The signal for Cat I is unlike those for the two peroxidases in that it reflects a ferromagnetic rather than antiferromagnetic exchange. Preliminary 1H ENDOR spectra for Cat I appear to differ from the proton (1H) ENDOR spectra of HRP I; the latter, along with the 14N ENDOR spectra, indicate that the porphyrin radical in HRP I exhibits a predominantly A2u-like state having large spin densities on porphyrin N and C(beta). The proton ENDOR spectrum of Cat I is insensitive to H/D exchange, which indicates that the [Fe = O]2+ moiety is not protonated. Consideration of the EPR results for a series of compounds I suggests that the sign and magnitude of the exchange parameter (J) is correlated with the nature of the proximal axial ligand.